(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study investigates the impact of design and operational standards on energy and water consumption in prison buildings in Saudi Arabia. The research aims to analyze energy efficiency and the controlling factors affecting energy performance within correctional facility infrastructure, focusing on technical standards and human behaviors as influencing variables. The study highlights those improvements in design elements, such as heating and cooling systems, building envelopes, the use of natural lighting, and renewable energy integration, can significantly enhance energy efficiency. It also emphasizes that building age and surrounding climatic conditions play crucial roles in determining energy consumption efficiency. On the operational side, factors such as user awareness, duration of their stay, and their willingness to contribute to energy efficiency, as well as the users' gender, affect energy consumption effectiveness. The research presents a case study of one of the largest and most recent prison facilities in Saudi Arabia, where water and energy consumption was measured based on official consumption invoices and records. The findings underscore the importance of adhering to appropriate design standards to reduce water and energy consumption and stress the need for comprehensive environmental studies before and during the design phase of prison buildings to achieve sustainability and resource efficiency goals.